Horner Syndrome Related to Nasopharyngeal Carcinoma - Nova Diana; Syntia Nusanti; M. Sidik (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Horner syndrome classically presents with ipsilateral blepharoptosis, pupillary miosis, and facial anhidrosis. The syndrome results from interuption of the sympathetic innervation to the eye and ocular adnexae. Case Illustration: A 43-year-old male complaining of drop of upper eyelid right eye, anhidrosis right side of face, and numbness on his right face since 7 months previously. He had painless, slowly enlarging, right-sided neck mass that was first noticed approximately 7 months before presentation. The biopsy and CT scan confirmed nasopharyngeal carcinoma (NPC). Best corrected visual acuity of both eyes was 6/6, normal IOP and ocular movement. There was mild ptotic eyelid 2 mm of his right eye. Both anterior segment within normal limit. There was unequal pupils greater in the dark, with pupil size of the right eye 3 mm and left eye 5 mm. The pupils were reactive to light, without afferent pupillary defect. Both posterior segment examination were unremarkable. There was reduced sensibility of the right face at maxila and mandibular region. The patient was diagnosed with Horner syndrome with involvement of right trigeminal nerve at maxillary and mandibular division, and involvement of sweat glands corellate with preganglionic lesion. Conclusion: Nasopharyngeal carcinoma that affects oculosympathetic pathway may give clinical signs as Horner syndrome. There was found involved of sweat gland in this case, it is correlated with lesion in preganglionic. But the anhidrosis occurs only in maxila and mandibular region, therefore post ganglionic involvement can not be ruled out. Keywords: Horner syndrome, nasopharyngeal carcinoma